Mindfulness-based treatment approaches : clinician's guide to evidence base and applications - Baer, Ruth A. (London : Academic Press, 2014)
"Mindfulness-based approaches are among the most innovative and interesting new approaches to mental health treatment. They are a "hot topic." Interest in them is widespread, with presentations and workshops drawing large audiences all over the US and many other countries. This book provides a comprehensive introduction to the best-researched mindfulness-based treatments. It emphasizes detailed clinical illustration providing a close-up view of how these treatments are conducted, the skills required of therapists, and how they work. The book also has a solid foundation in theory and research and shows clearly how these treatments can be understood using accepted psychological principles and concepts. The evidence base for these treatments is concisely reviewed"--EBL.
Part III. - Applications Across the Lifespan -- 8. - Mindfulness-Based Cognitive Therapy for Children -- Mindfulness-Based Cognitive Therapy for Children -- Theory And Concepts -- Empirical Support For Mindfulness As A Clinical Intervention -- Other Clinical Applications Of Mindfulness -- The 12-Session Program -- Affective And Behavioral Outcomes -- Practical Issues In Working With Children -- In Closing -- References -- 9. - Mindfulness-Based Stress Reduction for Teens -- Introduction -- Overview Of Mbsr-T -- Introducing Mindfulness To Teens -- Foundational Skills Of Mbsr-T -- Session-By-Session Outline For Mbsr-T -- Other Practices And Exercises -- Applying Mindfulness Skills To Teen-Specific Concerns -- Empirical Support For Mbsr-T -- Practical Issues -- Conclusions -- Acknowledgments -- References -- 10. - Mindfulness-Based Childbirth and Parenting: Cultivating Inner Resources for the Transition to Parenthood and Beyond -- Introduction -- Theoretical And Conceptual Foundations -- Overview Of Mbcp -- Case Study -- Empirical Support -- Practical Matters -- Conclusion -- References -- 11. - I Am Sure to Grow Old: Mindfulness-Based Elder Care -- Introduction -- Mindfulness-Based Elder Care -- Case Studies -- Empirical Evidence -- Practical Issues -- Future Directions -- Acknowledgment -- References -- Part IV. - Applications with Medical Populations -- 12. - Mindfulness-Based Stress Reduction for Chronic Pain -- Introduction -- Theoretical Foundation And Conceptual Rationale -- Case Study -- Review Of Empirical Support -- Practical Issues For Clinicians -- Conclusion -- Acknowledgment -- References -- 13. - Mindfulness-Based Cancer Recovery: An Adaptation of Mindfulness-Based Stress Reduction (MBSR) for Cancer Patients -- Theoretical And Conceptual Rationale -- Review Of Empirical Support -- Case Study -- Practical Issues -- Acknowledgments -- References -- Part V. - Applications for Work-Related Stress -- 14. - Mindfulness for Health Care Professionals and Therapists in Training -- Introduction -- Theoretical Foundations: What Is Mindfulness? -- Why Should Health Care Professionals Practice Mindfulness? -- Case Study:a Graduate Course In Mindfulness -- Conclusion -- References -- 15. - Mindfulness Training in High Stress Professions: Strengthening Attention and Resilience -- Theoretical And Empirical Foundations -- Mindfulness Training In The Legal Profession -- Case Study -- Conclusions.
Print version record.
Includes bibliographical references and indexes.
Keywords: Behavior therapy; Cognitive therapy; Meditation -- Therapeutic use; Behavior therapy; Cognitive therapy; Meditation -- Therapeutic use; MEDICAL / Pharmacology; Meditation -- methods; Behavior Therapy -- methods; Mindfulness -- methods; Electronic books; Electronic book